Analyzing the Use of Project-Based Learning in English Education: Enhancing Student Engagement and Communication Skills - Hendra Sudarso; Andi Nurhikmah; Much Deiniatur; Megawati, Megawati; Syam, Anugerah Febrian (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2024)
This study focuses on analyzing the effectiveness of Project-Based Learning (PBL) in the context of English language education, with an emphasis on student engagement and their communication skills. The research method employed in this study is quantitative, wherein the researchers evaluated significant changes in student engagement and communication skills after implementing PBL. The study involved two groups of students: an experimental group that implemented PBL and a control group that used traditional teaching methods as a comparison. The research findings indicate a significant improvement in learning motivation, active participation, and interest in the subject among students in the experimental group compared to the control group. Evaluation using posttest scores shows that students' abilities in speaking, listening, reading, and writing significantly improved in the experimental group that implemented PBL. This study indicates that to maximize the benefits of PBL in enhancing student engagement and communication skills in English language learning, strong support and training for educators are necessary, along with curriculum adjustments that align with the PBL approach.